(untitled) (Medico Legal Update, 2019)
Background/Objective: This paper aimed to select low-priced and high riced concealer products sold in Korea to analyze the inorganic materials in these cosmetic products and to investigate whether any heavy metal materials harmful to humans are present in them. Method: The inorganic materials and heavy metal materials in the concealer cosmetics products were observed with a scanning electron microscope and the component elements were analyzed using energy dispersion spectroscopy. Findings: Both the low- and high-priced concealer products used for this study mainly contained silica, titanium dioxide, and iron oxide. The study found that the high-priced concealer products did not contain heavy metal materials harmful to humans but the low-priced concealer products contained the radioactive material technetium. When cosmetics containing this radioactive material are applied over a long period of time adverse health and cosmetic effects may develop. Improvements/Applications: Not only stones and soil in nature but also metals in water may be mixed into the base materials used to manufacture cosmetics. High-purity base materials must be used to produce high-quality cosmetics and a thorough quality control process must be applied to the manufacturing process to prevent foreign materials from contaminating cosmetics products.